Cardiac resynchronization therapy in patients with heart failure: systematic review - Lemos Júnior, Hernani Pinto de (2009)
CONTEXT AND OBJECTIVE: Cardiac resynchronization therapy (CRT) has emerged as the predominant electrical treatment strategy for patients on pharmacological therapy who present heart failure with wide QRS and low ejection fraction. The objective of this study was to investigate whether cardiac resynchronization therapy improved mortality and morbidity among patients with heart failure. METHODS: This was a systematic review using the Cochrane Collaboration’s methodology. The online search strategy included the Cochrane Library, Medline (Medical Literature Analysis and Retrieval System Online), Lilacs (Literatura Latino-Americana e do Caribe em Ciências da Saúde) and cardiology congresses from 1990 to 2006. The criteria for considering studies for this review were as follows:-types of studies: randomized controlled trials; types of interventions: cardiac resynchronization therapy compared with other therapies; types of participants: patients with heart failure with low ejection fraction and wide QRS; outcomes: death or hospitalization. RESULTS: Seven trials met the selection criteria. The risk of death due to congestive heart failure was nonsignificant: relative risk (RR), 0.79; 95% confidence interval (CI): 0.60 to 1.03. There was an absolute risk reduction of 4% in all-cause mortality for the experimental group [RR 0.70; CI: 0.60 to 0.83; number needed to treat (NNT) 25]; sudden cardiac death showed a statistically significant difference favoring the experimental group, with absolute risk reduction of 1% (CI: 0.46 to 0.96; RR 0.67; NNT 100). There was an absolute risk reduction of 9% for hospitalization due to heart failure (RR 0.64; CI: 0.50 to 0.80; NNT 11) in the experimental group. CONCLUSIONS: Patients receiving CRT had a significantly lower risk of hospitalization due to heart failure, but death rates due to heart failure were similar.